Improvement of Electronic Correspondence of Inter-enterprise with Service Component of ECES - Mohammad Hadi Emtehani; Sima Emadi (Majlesi Journal of Electrical Engineering)
by development of using software of Enterprise Content Management (ECM), necessity of improving electronic Correspondence of inter-enterprise is felt more than before in order to enterprise cooperation. Despite existence of some bases for enterprise content management such as ECE protocol still there are some problems such as user intervention, delay, consumption of paper, parallelism, impossibility of tracking Correspondence and security problems and possibility of enterprise cooperation is not provided well. Using architecture of service component which has advantages of service-oriented approach such as simplicity, reusability, interoperability and flexibility produces an optimal solution for interoperability between systems and heterogeneous substrates by increasing the agility of integration of Web services meanwhile it doesnât have overload due to services and minimizes costs of development and maintenance. Component service of ECES which is implemented by using architecture of service component supports ECE standards and makes doing electronic Correspondence possible between enterprises of Iran.